Hospital Resilience in a Multi-Hazard Era: Water Security Planning in Northern Thailand - Alan D. Ziegler; Kampanat Wangsan; Phadungpon Supinit; Manoj Potapohn (Urban Science)
Hospitals require continuous access to water to sustain essential health services, especially when resources are taxed when drought conditions are compounded with other public health emergencies. In mid-2020, we conducted a rapid assessment of 71 hospitals in northern Thailand to evaluate water use and resilience during the concurrent 2019–2020 drought and the early phase of the COVID-19 pandemic in Thailand. While most hospitals reported adequate water availability, many depended on short-term measures such as shallow wells and improvised storage. Water use per bed often exceeded international benchmarks, reflecting broader usage patterns that extend beyond potable consumption. Community hospitals, in particular, reported more limited backup supply and planning capacity. Drawing on both our findings and international guidance, we propose the Hazard Management Model, involving a set of recommendations to strengthen hospital water resilience, including hazard-specific planning, protected infrastructure, emergency storage, and improved efficiency. These insights contribute to the growing body of work on climate-adaptive healthcare, particularly in resource-constrained settings facing intensifying multi-hazard risks.